Fastlane – Dynamic approach to low carbon and energy producing real estate portfolios – case Amsterdam Universities - Verhoeven, Thomas; Boeters, Rowan; Maassen, Wim (CLIMA 2022 conference, 2022)
In The Netherlands Municipalities, Universities and Healthcare organizations all have targeted to meet the Paris agreement targets, ‘Nett Zero Carbon’ namely 95% CO2-emission reductions compared to 1990, long before 2050. To support these organizations on their journey to meet their targets effective and efficient, regarding Carbon emissions as well as costs, a dynamic approach called FastLane is developed. FastLane has already been used for more than 1,000 buildings in more than 75 portfolio roadmap plans to reduce in total 1-3 Mton CO2 emissions by 2050. Implementing all these plans, we can reduce up to 1-3 Mton CO2 by 2050. This approach deals with three important challenges of the energy transition: only limited time and budget available, close the energy gap between calculated and measured Carbon emissions and provide a dynamic insightful tool to monitor and control the energy transition. These challenges require a different approach than traditional energy studies to identify and select measures. In this paper the requirements, demands and benefits of the developed approach, consisting of a methodology, smart tools using databases and strong insightful presentations in dashboards, are explained. The approach is illustrated with the case of University of Amsterdam & Amsterdam University of Applied Sciences with a combined portfolio of 50 buildings. Insights are given how Amsterdam University aims to reach their targets and how they are in control doing so during their journey. A roadmap with the most important renovation measures is presented including the possibilities of dynamic interventions adapting to possible changes in the future. Enabling an optimized timing of applying the measures. This already saved Amsterdam University up to 20% of the costs for the energy transition and optimizing the implementation along the way will guarantee the most effective and efficient energy transition of the real estate portfolio.